Interferensi Gramatikal Bahasa Bima terhadap Bahasa Indonesia Tulis Siswa SD - Sjafruddin A. Rahman (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2005)
This descriptive qualitative study aims to describe the variety of Bimaese grammatical interference into written Indonesian and the factors affecting the interference. Thirty-two fifth graders were involved in this study. The data were collected throught questionnaires, interviews, and observation. The findings suggest that there are a number of similarities and differences between Bimaese and Indonesian forms and that there is a transfer in terms of language components, system, and principles. The factors affecting these refer to linguistics, involving morphology and syntax, and non-linguistics, such as socio-linguistics, learning conditions, and socio-cultural factors.